Measurement of solubilities for supercritical fluid chromatography - Arvind Rajendran. (2010)
Supercritical fluid chromatography (SFC) is a technique that is finding attention in the pharmaceutical industry for the separation of enantiomers. Though the technology has been in existence for sometime especially in analytical applications, it is only in the recent years that industries are using them at preparative scales. The key difference between analytical and preparative SFC is that in preparative SFC very large flow rates are used in order to increase throughput. At these conditions two aspects affect the separation i) The solubility of the solute in the mobile phase and ii) Pressure drop across the column. These two aspects were analysed in this work. The solubility of a key non-steroidal anti-inflammatory drug in pure CO2 was successfully measured and modelled using two kinds of mathematical descriptions. The influence of pressure drop on column efficiency was successfully described using experiments and mathematical models. It was noticed that significant loss of column efficiency occurs at low operating pressure and low modifier concentrations. The key recommendation from this study can be summarized as follows: "SFC practitioners might find it advantageous to operate columns at higher back pressure settings especially at low modifier concentration to capitalize on the increased column efficiency.